2017
DOI: 10.2337/db16-0946
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Enrichment of Diabetogenic T Cells

Abstract: Dysfunctional T cells can mediate autoimmunity, but the inaccessibility of autoimmune tissues and the rarity of autoimmune T cells in the blood hinder their study. We describe a method to enrich and harvest autoimmune T cells in vivo by using a biomaterial scaffold loaded with protein antigens. In model antigen systems, we found that antigen-specific T cells become enriched within scaffolds containing their cognate antigens. When scaffolds containing lysates from an insulin-producing β-cell line were implanted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Notably, while the specific dMP formulation is tunable for disease-specific applications, the combination of agents in the dMP tested here synergized to influence T cell effector function. This may provide additional benefit in the case of antigenspecific T cell localization to a peripheral antigen depot, as recently reported in an antigen-defined T1D mouse model (87).…”
Section: Discussionmentioning
confidence: 73%
“…Notably, while the specific dMP formulation is tunable for disease-specific applications, the combination of agents in the dMP tested here synergized to influence T cell effector function. This may provide additional benefit in the case of antigenspecific T cell localization to a peripheral antigen depot, as recently reported in an antigen-defined T1D mouse model (87).…”
Section: Discussionmentioning
confidence: 73%
“…These findings are consistent with previous work. The same PLG-scaffold system used in this study was previously shown to enrich antigen-specific CD4 + and CD8 + T cells inside the scaffold when providing controlled delivery of either OVA or β cell lysate subcutaneously ( 24 ). Similarly, persistent presentation of gp100 melanoma peptide in incomplete Freund’s adjuvant, which protects the antigen from degradation, led to sequestration of antigen-specific CD8 + T cells at the vaccine site ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…To test this hypothesis, mice were first vaccinated using the model antigen ovalbumin (OVA) in the presence of aluminum (as a mimic for childhood vaccines) and later received an implantation of OVA-containing scaffolds in their ischemic hindlimbs. This vascularization strategy relies on (i) the widely accepted ability of aluminum as an adjuvant to generate memory T H 2 T cells when used in combination with an antigen ( 23 ) and (ii) our previous work demonstrating that antigen-containing polymer scaffolds can enrich for antigen-specific T cells to the scaffold site ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…Scaffolds provide a high level of control over the spaciotemporal presentation of self‐antigens and regulatory cues, and this ability can aid in directing the phenotype of infiltrating cells. Further, scaffolds can be retrieved after implantation or injection, serving as a unique mechanistic tool to monitor local immune response . The potential of harnessing scaffolds to engineer antigen‐specific immune response have been previously demonstrated by the Mooney group.…”
Section: Scaffolds Can Be Engineered To Promote Tolerancementioning
confidence: 99%